(untitled) (Third Sector Social Economic Review, 2025)
Asymmetry between countries denotes the disparity in political, economic, social, cultural, or military attributes among two or more states. This study seeks to assess the economic performance of Turkey and Greece from 1991 to 2023 via the lens of economic asymmetry utilizing the CRITIC and MARCOS methodologies. Eight specific economic evaluation criteria were employed to assess the economic performance of the countries: Gross Domestic Product (GDP), GDP per capita, inflation, total unemployment, exports of goods and services as a percentage of GDP, exports of goods and services in current USD, imports of goods and services as a percentage of GDP, and imports of goods and services in current USD. Consequently, it was determined that Turkey’s most effective economic performance was in 2013, while its least effective economic performance was in 1993. Greece’s peak economic performance occurred in 2008, but its lowest level was in 1998.